Sport, British national identities and the land: reflections on primordialism - Bairner, A.; May, A. (Sport in Society: Cultures, Commerce, Media, Politics, 2021)
The paper begins by outlining the key elements of the primordial approach to nations and nationalism central to which is the belief that national attachments and relations can be attributed to criteria that are perceived to be objective - language, ethnicity, geography - and which are likely to predate the emergence of the modern nation state and of nationalism as a modern political ideology. Although the approach is widely regarded with suspicion, evoking as it does the Nazi ideals of blood and soil, it nevertheless represents a valuable analytical tool for understanding the emotional attachment which many nationalists have to their natural landscape, whether real and imagined. Following a preliminary discussion of primordial theories of the nation, the paper then explains the two slightly different methodological approaches that have been used to examine two case studies which we argue demonstrate the value of a certain type of primordial perspective. Drawing upon autobiographies and biographies of former rugby union players from the Scottish border region, the first of these case studies examines the relationship between landscape, rugby union and culture in a unique part of the nation, not only in relation to its landscape, its most popular sport and the relationship between the two but also in terms of what it means to be Scottish. The second case study examines the relationship between sport, place and national identity in the industrial towns and cities of the English Midlands, drawing upon contemporary literature which discusses these concepts as defined by primordial ties to the land. Novels examined include Anthony Cartwright`s Heartland and Iron Towns.